Critical Analysis of the Research on Digital Literacy - Lela Susanty (Sinergi International Journal of Education, 2024)
Aim Research critical analysis will provide a comprehensive overview of the complexities inherent in digital literacy and its pivotal role in shaping the future of academic scholarship. This study uses a systematic literature review methodology to comprehensively examine digitalization initiatives in Digital Literacy Research. We conducted a comprehensive review of the existing literature on Critical Analysis of Digital Literacy Research. conclusion, the exploration of digital literacy and its impact on scholarly endeavors across diverse academic disciplines has shed light on the multifaceted ethical considerations and the need for tailored ethical guidelines and best practices. As we look towards the future of digital literacy research, it is crucial to adopt a forward-looking and adaptable approach that encompasses emerging technologies such as artificial intelligence, machine learning, and virtual/augmented reality. Understanding the influence of these technologies on digital competencies and their role in interdisciplinary collaboration will be pivotal in shaping the future landscape of collaborative scholarship. The synthesis of these policy considerations provides a comprehensive roadmap for bridging the gap in digital literacy and lays the groundwork for inclusive digital literacy initiatives. Moving forward, it is imperative for future research to delve into the enablers and barriers of implementing these policy recommendations in diverse academic settings. This will involve conducting case studies and collaborative research projects to assess the effectiveness of integrating digital literacy education into curricula and the impact of accessible digital resources on scholarly productivity and collaboration.